Nurse-led versus physician-led care models for MASLD: A comparative analysis of patient satisfaction in a Canadian tertiary centre - Nashla Hamdan-Pérez; Magdalena Kuczynski; Yoshihiro Yamamoto; Radin Pakseresht; Keyur Patel (Canadian Liver Journal, 2026)
Abstract Background: Metabolic dysfunction–associated steatotic liver disease (MASLD) is an increasingly prevalent public health issue that remains under-diagnosed, and patients frequently encounter systemic barriers. In our tertiary care setting, MASLD care is traditionally physician led. Long wait times (12–14 months) and high referral volumes necessitate alternative care models. In response, the registered nurse (RN)-led POWER (Patient Outcomes with Education and Resource) clinic was implemented. We aimed to evaluate and compare patient satisfaction between physician-led and RN-led MASLD clinics. Methods: We developed a 16-item patient satisfaction survey comprising three domains: provider performance (physician or nurse), patient-perceived support in achieving treatment goals, and overall clinic experience. Consecutive MASLD patients attending either ambulatory clinic were invited to complete the survey. Results: We received 152 completed surveys of 366 invitations, including 72% from the RN-led and 28% from the physician-led clinic. No statistically significant differences were found in performance between clinics. Patient satisfaction was high in both settings (RN clinic: 93.6%, physician clinic: 92.8%) and did not differ regarding provider listening ( p = 0.08) or understanding of the condition ( p = 0.86). Additionally, 88% of patients at the physician clinic and 81.4% at the RN clinic reported feeling more confident in achieving their lifestyle goals, although this was not statistically significant ( p = 0.23). Conclusions: Patient satisfaction with providers and perceived support was high across both MASLD clinics. Development and assessment of RN-led clinics is important given the need for task-shifting models of care to reduce wait times and risk stratification and to optimize MASLD management.